Comparative assessment of physicochemical properties of unripe peach (Prunus persica) and Japanese apricot (Prunus mume) - Kim, Hye-Ryun (Asian Pacific Tropical Medicine Press, 2014)
OBJECTIVE: To investigate the physicochemical properties of unripe peach-Prunus persica cv. Mibaekdo (Mibaekdo) and Prunus persica cv. Nagasawa Hakuho (Nagasawa Hakuho) as an alternative to food supplement while Japanese apricot (Prunus mume cv. Backaha) (Backaha) was used as a control sample. METHODS: The unripe fruits were analyzed for soluble solid ( ˚Brix), titratable acidity, pH, total polyphenol content, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, amygdalin content, free amino acid content, organic acid content, free sugar content, and α-amylase activities. RESULTS: Total polyphenol content of unripe peach ranged between 137.27-151.64 µg/g whereas that of apricot was 160.73 µg/g. DPPH radical scavenging activities of Backaha was the highest (89.16%) followed by Mibaekdo (85.05%) and Nagasawa Hakuho (41.50%). The highest amount of oxalic acid (612.8 mg/100 g) was observed in Mibaekdo while that of Nagasawa Hakuho and Backaha were (184.6±18.1) and (334.8±16.1) mg/100 g, respectively. Amygdalin contents of Mibaekdo, Nagasawa Hakuho and Backaha were 486.61, 548.60 and 174.28 µg/g, respectively. CONCLUSIONS: The results suggest that the unripe fruit of peach has a significant biochemical potential of using as a food supplement with potential health benefit for human health.